Kualitas Keripik Bengkuang (Pachyrrhizus erosus (L.) Urb.) dengan Variasi Konsentrasi Ekstrak Bunga Rosela (Hibiscus sabdariffa Linn.) - Martina Setyasih; F. Sinung Pranata; Ekawati Purwijantiningsih (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
Yam bean chips have crispy texture and sweet taste. In this research, rosella extract is added in the mold of yam bean chips as natural preservaties, fiber and sources anthocyanin. The aim of this research is to know the effect of various consentrations of rosella extract on chips qualities. Research design utilized was randomized complete factorial design and the data compiled was treated by Anova and followed with Duncan’s Multiple Range Test (DMRT) with degree of convidence 95%. Chips with 0,67% rosella extract added has longer shelf life than chips with out rosella extract added. This Chips contain 0,59% water, 2,6% protein, 38,84% fat, 3,69% ash, 54,16% carbohydrate, 1,17 mg/100g ascorbic acid, 1,4 mg/l anthocyanin, 1,17% acid total, 86,74%fiber crude, 53,47 level of lightness and total microorganism 30 CFU/G.